2008
DOI: 10.1002/ijc.23760
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and risk of endometrial cancer: A prospective study in Japan

Abstract: Coffee has been proposed to decrease the circulating insulin and estrogen levels, which are related to the development of endometrial cancer. However, few studies have prospectively assessed the association between coffee consumption and endometrial cancer. We conducted a population-based prospective cohort study in 53,724 Japanese women aged 40-69 years with no history of cancer at baseline in 1990-1994. We used Cox proportional hazards regression analysis to estimate the hazard ratio (HR) and 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
63
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 33 publications
10
63
0
Order By: Relevance
“…Concordant with previous prospective investigations, they report an overall inverse association for regular coffee consumption 2,3 and also report greater reduction among heavier women than in normal weight women. 3,4 The authors show statistically significant inverse associations for both caffeinated coffee and decaffeinated coffee, with per-cup hazard ratios of 0.90 (0.86-0.95) and 0.93 (0.87-0.99), respectively, and conclude that the observed reduction in endometrial cancer risk does not differ by caffeine content.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Concordant with previous prospective investigations, they report an overall inverse association for regular coffee consumption 2,3 and also report greater reduction among heavier women than in normal weight women. 3,4 The authors show statistically significant inverse associations for both caffeinated coffee and decaffeinated coffee, with per-cup hazard ratios of 0.90 (0.86-0.95) and 0.93 (0.87-0.99), respectively, and conclude that the observed reduction in endometrial cancer risk does not differ by caffeine content.…”
supporting
confidence: 87%
“…1 Original hazard ratios (95% CI), as presented in article ( Table 2). 2 Assumes <1 cup per day as the referent category and displays relative changes in hazard ratios for each coffee cup category. 3 Assumes 1 cup per day as the referent category and displays relative changes in hazard ratios for each coffee cup category.…”
mentioning
confidence: 99%
“…A hospital-based case control study from Italy, with 454 cases and a 2:1 control to case ratio, found the risk to be half at the upper quintiles of intake as compared to the lowest quintile (30). Two additional studies from Japan were published in 2008; one a population-based cohort of 53,724 women, 117 of which developed endometrial cancer during 15 years of follow-up (31), and the other a case control study with a similar number of cases (32)-both showed relative risks of 0.4 for those consuming 3 or more cups per day of coffee (cohort) or those in the upper tertile of consumption.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…In addition, several studies (meta-analyses, cohort, and casecontrol) have reported that coffee consumption is inversely associated with liver cancer (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Furthermore, studies that evaluated the coffee intake of HCC and HCV patients have suggested that a specific substance(s) in coffee could inhibit HCV infection and/or propagation (11,(26)(27)(28).…”
Section: Hepatocellular Carcinoma (Hcc) Is One Of the Most Common Canmentioning
confidence: 99%